WHY MICRO BUSINESS HAS NOT READY TO IMPLEMENT ACCOUNTING STANDARDS YET? - Pepie Diptyana; Rafi Fahmi Sandy; Erida Herlina (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
This study aims to describe the reasons of why micro businesses have not implemented accounting standards. We employ non-mainstream method with an interpretive paradigm. Data was collected by in-depth interviews and observations. Main informants of this study are leather craft entrepreneurs in Tanggulangin, Sidoarjo. Due to data validation, triangulation was carried out through interview with owner, three employees and one expert resource person, an active director of a venture capital company, and we also conduct document review. We found that entrepreneur has intention to implement record-keeping procedures, but have not been able yet to apply EMKM accounting standards due to: (1) limited knowledge about the importance of accrual-based accounting and company performance measurement; (2) skeptical attitude towards accounting and pragmatism in financial management; (3) limited human resources.